Peran Pesantren Makrifatul Ilmi dalam Moderasi Beragama pada Generasi Millenial - Ahmad Bahauddin AM; Suhaimi Suhaimi (JIA (Jurnal Ilmu Agama), 2022)
This article aims to analyze the role of Islamic boarding schools on religious moderation behavior in the millennial generation in Bengkulu Province, especially in the Makrifatul Ilmu Islamic Boarding School. The method used is qualitative through living culture and live in by being part of one of the students in order to obtain in-depth data. The results show that there are several attitudes taken by the Makrifatul Ilmi Islamic boarding school in South Bengkulu in order to realize the values ​​of religious moderation, these attitudes are: Tasamuh (tolerance), Ta'awun (please help), Tahaddur (civilized), Tatawwur wa ibtikar (dynamic and innovative). The conclusion is that the Makrifatul Ilmi Islamic Boarding School, South Bengkulu, instills the value of religious moderation properly and correctly. It can be seen in the programs carried out by Islamic boarding schools, both formal and non-formal education programs, all of which apply the values ​​of religious moderation.